Analysis Of Value Alignment Between Personal Beliefs And Corporate Social Responsibility In Retaining Generation Z Talent Within Creative Enterprises - Teguh Wahyudi (International Journal of Social Sciences, 2026)
This study investigates the alignment between personal values and Corporate Social Responsibility (CSR) initiatives as a critical factor in retaining Generation Z talent within creative enterprises. As this cohort prioritizes ethical authenticity over traditional incentives, understanding the mechanisms of value congruence is essential for organizational sustainability. A qualitative approach was employed, utilizing semi-structured interviews with 15 Generation Z professionals working in various creative firms in Indonesia. Data were analyzed using Thematic Analysis to identify recurring patterns regarding value alignment, ethical expectations, and retention drivers. The study reveals that Generation Z employees perceive CSR not merely as a corporate obligation but as a reflection of their personal identity. Three key themes emerged: (1) "Ethical Transparency" as a basis for trust, (2) "Impactful Participation" where talent seeks direct involvement in social initiatives, and (3) "Value Congruence" as a primary mediator for long-term commitment. Disconnects between corporate claims and actual practices (CSR-washing) were identified as a major catalyst for turnover. This research contributes to the burgeoning literature on talent management by providing a nuanced understanding of how personal-corporate value alignment functions specifically within the high-fluidity environment of creative industries, moving beyond generalized workforce studies.